2018
DOI: 10.3897/zookeys.808.30600
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Sphaerius Waltl from China (Coleoptera, Myxophaga, Sphaeriusidae)

Abstract: A new species, Sphaeriusminutussp. n., is described and illustrated from Jinggangshan Mts., Jiangxi Province, China. It is the first species of this family described from East Asia. This species lives under wet stones at the edge of rivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Hind wings with an oblongum, strongly reduced anal field and a complete fringe of hairs with helical structure. Aedeagus is well sclerotized, with a simple median lobe, short basally attached parameres and a small but well‐sclerotized phallobase (not examined for this study: Lawrence et al, 2011; Liang & Jia, 2018).…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hind wings with an oblongum, strongly reduced anal field and a complete fringe of hairs with helical structure. Aedeagus is well sclerotized, with a simple median lobe, short basally attached parameres and a small but well‐sclerotized phallobase (not examined for this study: Lawrence et al, 2011; Liang & Jia, 2018).…”
Section: Systematicsmentioning
confidence: 99%
“…However, data about species diversity within the family, natural history, or distribution remains extremely scarce. Twenty‐two species have been described, mostly based on randomly collected specimens and mostly diagnosed by the combination of body size and surface sculpture (e.g., Lesne, 1935; Liang & Jia, 2018; Matthews, 1899). The number of species and their distribution remains unclear, even for well‐studied regions like Europe and North America.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by Beutel & Raffaini (2003), due to the small size of sphaeriusids, detailed morphology for extant species can only be properly documented when SEM (scanning electronic microscopy) techniques are applied. However, only a few sphaeriusids have been imaged under SEM (e.g., Löbl, 1995;Liang & Jia, 2018;Yavorskaya et al, 2018;Fikáček et al, 2022), and some of them were not identified to species level (e.g., Beutel, 1999;Beutel & Raffaini, 2003;Kamezawa & Matsubara, 2012). As a result, the taxonomy of this group has been insufficiently studied and the its species-level diversity is likely strongly underestimated (Fikáček et al, 2022).…”
Section: Introductionmentioning
confidence: 99%